Bible and Theology from the Underside of Empire - Vellem, Vuyani (African Sun Media, 2017)
'Empire' has become an apt label to name the present horizon of global life and is associated with logic and practices which threaten human life in myriad ways. These reflections not only expose the true nature of empire, but suggest an alternative vision of flourishing wrought by God's kingdom. In a creative and imaginative manner the contributions highlight new liberative possibilities for life through non-conventional Bible reading. The authors display a sensitive moral antenna for the oppressive manifestations of empire, and courageously intimate a new paradigm for Christian mission and public witness today.